Innovative pricing strategies to increase profits - Marburger, Daniel R. (Economics collection., 2015)
The practice of setting a single price that all buyers pay is slowly becoming a thing of the past. Today's marketplace requires firms to develop innovative pricing strategies to remain competitive. Is it better to bundle goods or price them separately? What type of online auction will generate the most revenue? The purpose of this book is to use microeconomic theory to determine which pricing strategies will succeed, and under what conditions.